The effects of physical activity on some physiological indices of mother and neonate - Seyed Ali Hosseini; Niloofar Arabpour; Nasibeh Kazemi; Saeedeh Shadmehri; Iman Fathi (Hygeia Press di Corridori Marinella, 2021)
Background: Physical activity can bring about more favorable health results for both mother and neonate. Objectives: The purpose of this study was to investigate the effect of physical activity on some physiological indices of mother and neonate. Design and methods: In this ex post facto study, 60 pregnant women (age 26.9 ± 4.0 years, height 161.8 ± 5.2 cm and weight 63.0 ± 4.9 kg) were selected from health centers and private clinics in Shiraz, Iran. Based on the score obtained from completion of a physical activity questionnaire during pregnancy, the participants were classified into 4 groups: 1) active, 2) inactive, 3) becoming active, and 4) becoming inactive. The maternal type of delivery, body weight and body fat percentage, as well as the neonatal birth weight and height and Apgar score at 1 and 5 minutes, were measured. To analyze the data, a one-way ANOVA and Tukey's post hoc test were used at the level of p ≤ 0.05. Results: The mean weight gain in pregnant women in the active group was significantly lower than that of the inactive group (p ≤ 0.05), but there was not a significant difference between the becoming active and becoming inactive groups (p > 0.05). Participation in physical activity does not affect the body fat percentage and type of pregnancy in pregnant women (p > 0.05). Additionally, participation in physical activity does not have a significant effect on the neonate's growth and health (p > 0.05). Conclusions: It seems that although the participation of pregnant mothers in physical activity is associated with a lower weight gain in pregnancy, there is no significant effect on other physiological indices of mother and neonate.